Algebraic Manupulation

Algebra Level 1

If a b = 15 ab = 15 and a 2 + b 2 = 40 a^2 + b^2 = 40 , then find the value of ( a + b ) 4 ( a b ) 4 (a+b)^4 - (a-b)^4 .

3600 4098 4096 4800 1200 2400

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Akash Patalwanshi
May 13, 2016

a b = 15 2 a b = 30 , 2 a b = 30 ab = 15 → 2ab = 30, -2ab = -30

a 2 + b 2 + 2 a b = ( a + b ) 2 = 40 + 30 = 70 → a^2 + b^2 +2ab = (a+b)^2 = 40 + 30 = 70

a 2 + b 2 2 a b = ( a b ) 2 = 40 30 = 10 a^2 + b^2 -2ab = (a-b)^2 = 40-30 = 10

( a + b ) 4 ( a b ) 4 = 7 0 2 1 0 2 →(a +b)^4 - (a-b)^4 = 70^2 -10^2

= ( 70 + 10 ) ( 70 10 ) = 80 × 60 = 4800 = (70 +10)(70-10) = 80\times60 =\boxed{4800}

Munem Shahriar
Sep 16, 2017

Given that,

  • a 2 + b 2 = 40 a^2 +b^2 = 40

  • a b = 15 ab = 15

Now,

( a + b ) 4 ( a b ) 4 (a+b)^4 - (a-b)^4

= { ( a + b ) 2 } 2 { ( a b ) 2 } 2 = \{(a+b)^2\}^2 - \{(a-b)^2\}^2

= ( a 2 + 2 a b + b 2 ) 2 ( a 2 + 2 a b b 2 ) 2 = (a^2 + 2ab+b^2)^2 - (a^2+2ab - b^2)^2

= ( a 2 + b 2 + 2 a b ) 2 ( a 2 + b 2 2 a b ) 2 =(a^2+b^2 +2ab)^2 - (a^2+b^2-2ab)^2

= { 40 + 2 ( 15 ) } 2 { 40 2 ( 15 ) } 2 =\{40+2(15)\}^2 - \{40 - 2(15)\}^2

= ( 40 + 30 ) 2 ( 40 30 ) 2 = (40 + 30)^2 - (40 - 30)^2

= ( 70 ) 2 ( 10 ) 2 = (70)^2 - (10)^2

= 4800 = \color{#20A900} \boxed{4800}

BREAK THESE TYPE OF SUMS IN THE FORMULA

{a+b}{a+b}

ab=15

therefore

{a+b}{a+b}=40+{2 X 15}

{a-b}{a-b}=40-{2 X 15}

thx for solution

Saraswat Bhattacharya - 4 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...